Fluocinolone acetonide partially restores the mineralization of LPS‐stimulated dental pulp cells through inhibition of NF‐κB pathway and activation of AP‐1 pathway. (28th October 2013) - Liu, Zhongning; Jiang, Ting; Wang, Xinzhi; Wang, Yixiang
Abstract : Background and Purpose: Fluocinolone acetonide (FA) is commonly used as a steroidal anti‐inflammatory drug. We recently found that in dental pulp cells (DPCs) FA has osteo‐/odonto‐inductive as well as anti‐inflammatory effects. However, the mechanism by which FA induces these effects in DPCs is poorly understood. Experimental Approach: The effect of FA on the mineralization of DPCs during inflammatory conditions and the underlying mechanism were investigated by real‐time PCR, Western blot, EMSA, histochemical staining, immunostaining and pathway blockade assays. Key Results: FA significantly inhibited the inflammatory response in LPS‐treated DPCs not only by down‐regulating the expression of pro–inflammation‐related genes, but also by up‐regulating the expression of the anti‐inflammatory gene PPAR‐γ and mineralization‐related genes. Moreover, histochemical staining and immunostaining showed that FA could partially restore the expressions of alkaline phosphatase, osteocalcin and dentin sialophosphoprotein (DSPP) and mineralization in LPS‐stimulated DPCs. Real‐time PCR and Western blot analysis revealed that FA up‐regulated DSPP and runt‐related transcription factor 2 expression by inhibiting the expression of phosphorylated‐NF‐κB P65 and activating activator protein‐1 (AP‐1) (p‐c‐Jun and Fra‐1). These results were further confirmed through EMSA, by detection of NF‐κB DNA‐binding activity and pathway blockade assays using a NF‐κB pathway inhibitor, AP‐1 pathway inhibitor and glucocorticoid receptor antagonist. Conclusions and Implications: Inflammation induced by LPS suppresses the mineralization process in DPCs. FA partially restored this osteo‐/odonto‐genesis process in LPS‐treated DPCs and had an anti‐inflammatory effect through inhibition of the NF‐κB pathway and activation of the AP‐1 pathway. Hence, FA is a potential new treatment for inflammation‐associated bone/teeth diseases.